Development of Ice Jellyger Beverage Products as a Business to Train the Spirit of Entrepreneurship Among Students Through Social - Maida Oktalia; Anisa Hasanah; Puri Maharani; Eko Risdianto (CV. Media Inti Teknologi, 2024)
In addition to marketing products through social media and having an entrepreneurial spirit, sellers or students or entrepreneurs must choose a business that is contemporary and can compete in the social media market such as the Es Jellygar (Fresh Jelly) beverage product business. This research aims to train the spirit of entrepreneurship among students in developing and marketing Ice Jellygar beverage products. This research is an R&D research, the development model used is the 4D model (Define, Design, Develop, and Disseminate). The data analysis method used in this study was carried out through product acceptance tests on consumers. The result of this research is the development of Es Jellygar beverage products, which go through four stages of development: Define, Design, Develop, and Disseminate. The Define stage focuses on finding reference recipes, the Design Stage creates prototypes or product designs, the Develop Stage involves evaluation by experts and prototype testing, and the Disseminate Stage is about introducing products to the public through exhibitions and consumer testing. Marketing products through social media and having an entrepreneurial spirit, sellers or students or entrepreneurs must choose businesses that are contemporary and can compete in the social media market such as the Es Jellygar (Fresh Jelly) beverage product business. So it can be concluded that this business can be an opportunity for entrepreneurs or students as an easy side business, and can compete in the sales field.